Social Engineering Educational System: SECURIFY - Khairin Chan, Ibrahim Chan (2023)
The growing prevalence of social engineering attacks poses a significant threat to individuals and organizations alike. To mitigate this risk, there is a pressing need for effective educational systems that promote awareness and understanding of social engineering tactics. This thesis presents the development of a comprehensive Social Engineering Educational System, named "Securify," aimed at equipping users with the knowledge and skills necessary to recognize and defend against social engineering attacks. Securify incorporates a range of interactive features designed to engage and educate users. The system offers quizzes that simulate real-life social engineering scenarios, allowing users to test their knowledge and decision-making abilities. Furthermore, educational materials, including tutorials, videos, and case studies, are provided to enhance users' understanding of various social engineering techniques and countermeasures. Additionally, the system incorporates a news and blog section, which offers the latest updates on social engineering trends and best practices. The development of Securify involved a meticulous research phase, where an extensive analysis of prevalent social engineering tactics was conducted. This research served as the foundation for the creation of scenario-based quizzes and educational content that reflect real-world social engineering scenarios. To evaluate the effectiveness of Securify, a user study was conducted involving participants from diverse backgrounds. The results demonstrated a significant improvement in participants' awareness and knowledge of social engineering, as well as an enhanced ability to identify and respond to potential social engineering attacks. The Social Engineering Educational System, Securify, fills a crucial gap in security education by providing users with a comprehensive and interactive platform to learn about social engineering threats. The system's user-centric approach and engaging features empower individuals and organizations to develop a proactive defense against social engineering attacks, thereby strengthening overall security posture.